PELAKSANAAN PERJANJIAN KERJASAMA PENYALURAN LPG 3 KILOGRAM, ANTARA PT. VALERY FAMILY SEJAHTERA DAN PANGKALAN UD. MAJU JAYA DI KOTA PEKANBARU - Togu Rizky Anggel; Evi Deliana; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
3 Kilograms of LPG gas is an essential requirement for supporting the life of every community. The distribution of 3 Kilogram LPG gas is carried out by the private sector, which is the agent of the arm of the first party, the principal. The agent and sub-agent cooperate on the basis of the agreement made. 3 Kilograms of gas that were distributed to the base were aimed at people in need. In Article 1313 of the Civil Code, an agreement is an act whereby one or more people bind themselves to one or more people. The agreement made between the base and the agent is a standard cooperation agreement. The agreement that has been agreed must be carried out as well as possible. If the parties do not run it well, there will be losses for those who carry out their achievements. The problems and objectives that will be discussed in this thesis are to determine the implementation of the 3 Kilogram LPG distribution agreement between PT. Valery Family Sejahtera and Pangkalan UD. Maju Jaya in Pekanbaru City.This type of research is sociological, because in this study the author directly conducts research at the location or place under study in order to provide a complete and clear picture of the problem under study. This research was conducted at Pangakalan UD. Maju Jaya and PT. Valery Family Sejahtera in Pekanbaru City, while the population and sample are all parties related to the problems studied in this study, the data sources used, primary data and secondary data, data collection techniques in this study with interviews, questionnaires and literature study.The results of the study concluded that the implementation of the agreement between PT. Valery Family Sejahtera based on UD. Maju Jaya in the distribution of 3 Kilogram LPG gas has not been carried out properly. The agents encountered obstacles and obstacles in distributing 3 Kilogram of LPG gas to the base making the agreement difficult to implement.Keywords: Implementation, Agreement, Distribution